Multicomponent intervention for schoolchildren with asthma: Pilot cluster randomized controlled trial - Marina Reznik, MD, MS; Florinda Islamovic, MD; Jill S. Halterman, MD, MPH; Cheng-Shiun Leu, PhD; Jiaqing Zhang, PhD; Philip O. Ozuah, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Physical activity (PA) is an important factor in asthma management. However, studies report low PA in children with asthma living in underserved communities. Objective: We assessed preliminary effectiveness of a pilot multicomponent asthma intervention that includes classroom-based PA, asthma education to increase knowledge and reduce stigma, and care coordination to facilitate guideline-based care, on PA and symptom-free days (SFD) in urban, historically marginalized children with asthma. Methods: Children aged 7-10 years with asthma and their caregivers were recruited from 4 Bronx, NY, schools. We randomly assigned 2 schools as intervention and 2 as control sites. Child PA (primary outcome) was measured by accelerometers at 4 time points, and caregivers completed surveys on asthma symptoms. Analyses used generalized linear mixed models with generalized estimating equation adjusting for clustering. Clinical Trial Registration: ClinicalTrials.gov NCT01873755. Results: We included 107 children (53% male participants, 82% Hispanic, mean [standard deviation] age 9.0 [1.0] years, 76% with persistent or uncontrolled asthma). Children in the intervention group had a significantly greater increase in total moderate-to-vigorous PA and step counts at 12 months after intervention in the entire sample (β = 6.05, P < .0001; β = 579.11, P = .008, respectively) and in those with persistent or uncontrolled asthma compared to controls (β = 6.20, P < .001; β = 639.08, P = .004, respectively). Similar beneficial intervention effects were found in improvement in SFD over 2 weeks in the entire sample (β = 1.38, P = .018) and in children with persistent or uncontrolled asthma (β = 1.82, P = .011) compared to controls. Conclusion: A pilot intervention addressing multiple barriers to PA, including stigma, teacher confidence in asthma management, access to PA, and in-school medication, improved PA levels and SFD in students with asthma.